1998
DOI: 10.1023/a:1008831209706
|View full text |Cite
|
Sign up to set email alerts
|

The problem of measuring change in individual health-related quality of life by postal questionnaire: use of the patient-generated index in a disabled population

Abstract: The Patient-generated Index (PGI) is a health-related quality of life (HRQoL) measure which asks respondents to nominate the areas of their lives which are most affected by their health condition, so that they can then rate the severity of the effects and weight their relative importance. It is unusual amongst such measures in that it is designed for postal administration. This study assessed the ability of the revised PGI to measure change in HRQoL in a population of 161 people who had previously been identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 11 publications
3
35
1
5
Order By: Relevance
“…Many subjects in our study also expressed difficulty understanding what was meant by 'all other non-health areas', a problem found with other study populations [10,27]. Previous studies which administered the PGI through postal questionnaires reported response rates of 65% in a disabled population [10], 74% for patients with low back pain [9], and 77% for a group of arthritic patients [28].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Many subjects in our study also expressed difficulty understanding what was meant by 'all other non-health areas', a problem found with other study populations [10,27]. Previous studies which administered the PGI through postal questionnaires reported response rates of 65% in a disabled population [10], 74% for patients with low back pain [9], and 77% for a group of arthritic patients [28].…”
Section: Discussionmentioning
confidence: 62%
“…Individualized measure of HRQL The PGI [8][9][10] was used to evaluate individualized HRQL and to provide a structure for asking subjects to express the areas important for their HRQL. There are three steps to completing this measure.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is unclear whether this association is due to the most relevant examples being selected from the prompt list, or due to respondents being unwilling or unable to think of their own examples because the prompt list is already comprehensive. 104 We correlated the mean PGI score with the mean EQ-5D scores. This correlation was, as expected, found to be positive and statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Some people have difficulty understanding the system of direct weighting, thus limiting their use as self completed questionnaires (e.g. Macduff and Russell 1998). Individualized measures are also dependent on respondents volunteering domains of QoL important to them.…”
Section: Quality Of Life In Prosthetic Practicementioning
confidence: 99%